Mathematical Modeling on Vacuum Drying of Olive Pomace - Maamar, Mouhcine Ibn; Badraoui, Mohamed; Mazouzi, Mohamed; Mouakkir, Laila (Trends in Sciences, 2022)
Abstract: The thin-layer olive pomace vacuum drying behavior was experimentally investigated for 3 gauge pressures; −130, −200, −250 mbar, and for various sample thicknesses 5, 10 and 15 mm. Nine thin layer mathematical models were used to fit olive cake vacuum drying. Olive pomace vacuum drying took place in the falling rate period at all pressures and for all thicknesses, no constant rate period was observed. Among the selected models, the Diffusion Approach was found to be the most appropriate model better describing the olive pomace drying behavior. The drying rate is correlated to the depression under the thin layer and its thickness. ANOVA-Pareto variance analysis showed the predominance of gauge pressure over layer thickness on drying time and drying rate. The diffusivity coefficient increased linearly over the depression range, from 3.37657E-09 to 4.03063E-06 m2/s, as obtained using Fick’s second law. HIGHLIGHTS Olive oil world production reached 3.300.000 tons in the 2020 campaign, leaving behind high quantities of oil residues mainly olive pomace harmful to the environment Olive pomace valorization is challenging due to its richness in moisture, drying is, therefore, an essential part of its recovery This research studies pomace vacuum drying for different gauge pressures and layer thicknesses Olive pomace drying rates are falling for all pressures and thicknesses The Diffusion Approach mathematical model better describes the process of olive pomace vacuum drying This research finding helps improve drying conditions and parameters of vacuum dryers GRAPHICAL ABSTRACT